P114 Tissue regeneration and bone repair upon TNF blockade in experimental arthritis. (March 2019) - Wanic, K; ,; Kalkgruber, M; Niederreiter, B; Shvets, T; Smolen, J; Hayer, S
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Partial bone repair upon treatment with biological DMARDs has been reported in patients with Rheumatoid Arthritis (RA). Previous in vivo PET/CT studies using the human tumor necrosis factor transgenic mouse model (hTNFtg) have been demonstrated the reversibility of pre-existing inflammatory, erosive arthritis with complete remission of synovial inflammation and repair of bone erosions upon TNF blockade. Objectives: To investigate spontaneous repair and regenerative processes of structural joint damage in ankle and knee joint, menisci and patella tendon upon TNF blockade in hTNFtg mice. Methods: Two cohorts of arthritic hTNFtg mice were treated with anti-TNF ab (infliximab, 10 mg/kg, 3x per week, i.p., 4 weeks): (I) 8 week old mice with established inflammatory, erosive arthritis and (II) 12 week old hTNFtg mice with severe inflammatory, erosive arthritis (n=8–10 animals). Clinical signs of arthritis were weekly assessed. Knee and ankle joints were used for µCT (Scanco µCT35) and subsequent histology. Toluidine blue staining indicated proteoglycan contents, tartrate-resistant acid phosphatase staining identified osteoclasts. Immunohistochemical stainings were performed for collagen type II (col II) and osterix. Expression of chondrogenic markers was analysed from RNA paw extracts. Results: TNF blockade significantly improved clinical signs in both treatment cohorts. Compared to eroded bone surfaces at week 8 (before treatment), TNF blockade led to improved bone architecture with regular, smooth bone surfaces in CT scans from knee and ankle. Histologically, treatment allowed complete resolution of synovitis, osteoclast activity and subchondral bone erosions. Despite sites of intact bone tissue, regenerative processes of cortical and subchondral bone were found. Erosions of bone and calcified cartilage were filled with col II positive cartilaginous or fibro-cartilaginous tissue. Hyperproliferative chondrocytes and endochondral ossifications were found in knees. Consistently, chondrogenic markers like Sox9 transcription factor and col II were markedly increased, accompanied by decreased expression of cartilage degrading enzymes (MMP3, MMP13) upon treatment. Of note, menisci and patella tendon showed massive hyperproliferative chondrocytes, col II and osterix staining. Anti-TNF treatment at later stages with severe bone destruction (at week 12) could not completely resolve synovitis and restore structural damage. Pannus tissue transformed into chondrocyte rich, fibrocartilaginous tissue. Callus and ossifications were formed in knees. Conclusions: Therapeutic TNF blockade of inflammation-mediated joint damage enables the initiation of directed but also undirected regenerative processes. Remission of synovitis seems to be essential to promote bone and calcified cartilage repair. Disclosure of Interest: None declared.